Plasma GDF-15 concentration is not elevated in open-angle glaucoma. - Wouter H G Hubens (Public Library of Science (PLoS), 2021)
Aim Recently, the level of growth differentiation factor 15 (GDF-15) in blood, was proposed as biomarker to detect mitochondrial dysfunction. In the current study, we evaluate this biomarker in open-angle glaucoma (OAG), as there is increasing evidence that mitochondrial dysfunction plays a role in the pathophysiology of this disease. Methods Plasma GDF-15 concentrations were measured with ELISA in 200 OAG patients and 61 age-matched controls (cataract without glaucoma). The OAG patient group consisted of high tension glaucoma (HTG; n = 162) and normal tension glaucoma (NTG; n = 38). Groups were compared using the Kruskal-Wallis nonparametric test with Dunn's multiple comparison post-hoc correction. GDF-15 concentration was corrected for confounders identified with forward linear regression models. Results Before correcting for confounders, median plasma GDF-15 levels was significantly lower in the combined OAG group (p = 0.04), but not when analysing HTG and NTG patients separately. Forward linear regression analysis showed that age, gender, smoking and systemic hypertension were significant confounders affecting GDF-15 levels. After correction for these confounders, GDF-15 levels in OAG patients were no longer significantly different from controls. Subgroup analysis of the glaucoma patients did not show a correlation between disease severity and plasma GDF-15, but did reveal that for NTG patients, intake of dietary supplements, which potentially improve mitochondrial function, correlated with lower plasma GDF-15. Conclusion The present study suggests that plasma GDF-15 is not suited as biomarker of mitochondrial dysfunction in OAG patients.